Profil Daya Tahan Kardiorespirasi Peserta Ekstrakurikuler Futsal SMPN 6 Yogyakarta - Mustofa, Hanafi Mustofa; Wahyu Wibowo Eko Yulianto (Universitas PGRI Yogyakarta, 2023)
This study aims to describe the cardiorespiratory endurance of futsal extracurricular participants at SMPN 6 Yogyakarta for the 2023/2024 academic year. This research is a quantitative descriptive research, the research will be carried out in October 2023 at the futsal field of SMPN 6 Yogyakarta. The sample of this study was 31 futsal extracurricular participants, a sampling technique using total sampling techniques. The data collection technique uses the Multistage Fitness Test (MFT) test with a test validity value of 0.744 and test reliability of 0.697. The data analysis technique in this study used a table of Multistage Fitness Test (MFT) phase D test norms, then continued with percentage descriptive analysis. The results of the study can be seen that the Cardiorespiratory Endurance of Futsal Extracurricular Participants at SMPN 6 Yogyakarta is included in the Very Good category as many as 11 students (35.48%), is included in the Good category as many as 15 students (48.39%), is included in the Medium category as many as 5 students (16.13.00%), is included in the Less category as many as 0 students (0%), and is included in the Less once category as many as 0 students (0.00%). Based on an average value of 34.16 or Level 6 Balikan 4, it can be concluded that the ability of Cardiorespiratory Endurance in Futsal Extracurricular Participants at SMPN 6 Yogyakarta is included in the Good category. Cardiorespiratory endurance as one of the indicators to describe the physical fitness of futsal extracurricular participants Keyword: Cardiorespiirated Endurance, Physical Fitness, Futsal Player, Futsal Extracurricular